ANALISIS MUTU NUGGET IKAN PISANG-PISANG (Casieo crhysozon) DENGAN PENAMBAHAN WORTEL - Rahmiah, Andi Nur; Syam, Husain; Sukainah, Andi (Universitas Negeri Makassar, 2018)
This study aims to determine the quality analysis of banana fish nuggets (Caesio chrysozon) with the addition of carrots. The study used a completely randomized design (CRD) factorial pattern of factors, namely fish concentration and carrot concentration with a treatment of nine and three replications. The treatment in this study was A1B0 = 250 g fish + 0 g carrots, A2B0 = 300 g fish + 0 g carrots, A3B0 = 350 g fish + 0 g carrots, A1B1 = 250 g fish + 25 g carrots, A2B1 = 300 g fish + 25 g carrots, A3B1 = 350 g fish + 25 g carrots, A1B2 = 250 g fish + 50 g carrots, A2B2 = 300 g fish + 50 g carrots, A3B1 = 350 g fish + 50 g carrots. Observation data were analyzed using Variance Analysis (ANOVA) then continued with Ducan Test. The results showed that fish concentration and carrot concentration had an effect on water content, fat content, protein content, vitamin A, color, aroma, taste, texture. The best treatment of banana fish nuggets with the addition of carrots is the treatment A2B1 = 300 g fish + 25 g carrots, moisture content (45.58%) protein content (14.56%) fat content (3.82%), vitamin A (0.011%) color (3.64% likes) aroma (3.68% likes), taste (3.83% likes), texture (3.61% likes).